Analisis Profitabilitas Bank Syariah Swasta di Indonesia sebelum dan Sesudah Covid -19 (Dengan Menggunakan Metode Horizontal) - Khoiriyah, Ummi; Syam, Andi Hunafah Balqis; Larasati, Larasati; Maulana, Moh. David; Rahmawati , Rafika (Shafin: Sharia Finance and Accounting Journal, 2022)
Abstract: This study aims to analyze the profitability of private Islamic banks in Indonesia before and after Covid-19 (using the Horizontal method). This research is a type of quantitative research. Quantitative data used in this study is the calculation of total assets, net income and total capital in BCA Syariah banking, Victoria Syariah bank, Maybank Syariah bank, and CIMB Niaga Syariah bank. The data sources are obtained from the financial statements of BCA Syariah banks, Victoria Syariah banks, Maybank Syariah banks, and CIMB Niaga Syariah banks which are available on the official website of the Financial Services Authority (OJK) for 2018, 2020, and 2021 in the form of report data on Total Assets, Total Capital and Net profit. Using the calculation of ROA and ROE profitability ratios to be able to analyze with horizontal analysis, comparing from 2018 to 2021, where the base year used is 2018. The results showed that the profitability ratios of BCA Syariah banks and Maybank Syariah banks experienced a decrease in profitability while Victoria Syariah banks and CIMB Niaga Syariah banks experienced increased profitability during the covid-19 pandemic.